The Clarity of Conversion: Enabling Transformational Conversion in Germany - Frank R. Liesen (Voice, 2022)
Transformational conversion has been essential to the cross-cultural diffusion of Christianity. An introduction to conversion and diffusion in the New Testament reveals relevant biblical themes to ensure an intelligible communication of conversion from an evangelical viewpoint. Conversion requires a two-fold movement of repentance from sin and faith in Jesus Christ. As a supernatural act of God, people respond to the verbal transmission of the gospel with a personal decision of faith. The biblical data supplies that conversions may involve deliberation processes and cannot be separated from a life-long commitment to Christian discipleship. A multi-case study of three church plants in Germany confirms that clear invitations into discipleship are necessary for facilitating transformational conversion. Each church presented conversion intelligibly, provided decision-making opportunities, affirmed the point and process of conversion, and connected conversion with discipleship.